Europe's Automotive Industry on the Move Competitiveness in a Changing World - Heneric, Oliver.; Heneric, Oliver.; Licht, Georg.; Licht, Georg.; Sofka, Wolfgang.; Sofka, Wolfgang. (ZEW Economic Studies, 2005)
The automotive industry is a major pillar of the modern global economy and one of Europe’s key industries. There can hardly be any doubt about the important role of this sector as an engine for employment, growth and innovation in Europe, and there are crucial challenges and opportunities ahead. The authors shed light on a broad range of issues – globalisation and restructuring, trade and foreign direct investment, innovation, regulation, and industry policy – and put a special focus on the new member states. While change may be inevitable, progress is not. This book shall serve as a map to all stakeholders: business executives and policy makers, investors and scholars.